2015
DOI: 10.1155/2015/593014
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Biosynthesized Zinc Oxide Nanoparticles on Murine Cell Lines

Abstract: The aim of this study is to evaluate the in vitro cytotoxic activity and cellular effects of previously prepared ZnO-NPs on murine cancer cell lines using brown seaweed (Sargassum muticum) aqueous extract. Treated cancer cells with ZnO-NPs for 72 hours demonstrated various levels of cytotoxicity based on calculated IC50 values using MTT assay as follows: 21.7 ± 1.3 μg/mL (4T1), 17.45 ± 1.1 μg/mL (CRL-1451), 11.75 ± 0.8 μg/mL (CT-26), and 5.6 ± 0.55 μg/mL (WEHI-3B), respectively. On the other hand, ZnO-NPs trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 37 publications
(42 reference statements)
7
54
0
Order By: Relevance
“…[9][10][11][12][13] The toxicity of ZnO NPs has been shown to be attributed to the dissolution of Zn to free Zn 2+ ions and the generation of free radicals from the surface of ZnO, resulting in cellular ionic and metabolic imbalance that is associated with a defect in ionic homeostasis and an inhibition of ion transport. 9,12,14,15 In vitro toxicity studies revealed that generation of reactive oxygen species (ROS), followed by ROS-induced oxidative stress, is the mechanism leading to the ZnO NP-mediated toxicity. Insufficient antioxidative protective mechanism following excessive ROS production, has shown to elicit cell death and genotoxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] The toxicity of ZnO NPs has been shown to be attributed to the dissolution of Zn to free Zn 2+ ions and the generation of free radicals from the surface of ZnO, resulting in cellular ionic and metabolic imbalance that is associated with a defect in ionic homeostasis and an inhibition of ion transport. 9,12,14,15 In vitro toxicity studies revealed that generation of reactive oxygen species (ROS), followed by ROS-induced oxidative stress, is the mechanism leading to the ZnO NP-mediated toxicity. Insufficient antioxidative protective mechanism following excessive ROS production, has shown to elicit cell death and genotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient antioxidative protective mechanism following excessive ROS production, has shown to elicit cell death and genotoxicity. 14 Other than the inherent properties of ZnO NPs, physicochemical properties, such as size and surface charges contribute to the toxicity of ZnO NPs. In addition to the phase (amorphous, anatase, etc) and contact area between a single nanoparticle (NP) and a single cell, smaller and rod shaped nano ZnO (in comparison to spherical shape) is reported to be more toxic.…”
Section: Introductionmentioning
confidence: 99%
“…The increased use of ZnO NPs in consumer products on the market and the devastating long-term damage they potentially cause to humans have prompted increased assessment of their adverse effects in vitro and in vivo. 9,10 Several studies have reported the cytotoxic and genotoxic potential of ZnO NPs using in vitro assays in immune cells, lung epithelial, and cancer cells. [11][12][13][14] Johnson et al showed that the exposure of immune cells to ZnO NPs resulted in increased levels of the autophagosome protein LC3A and, consequently, autophagic death, which were inhibited by blocking autophagy and reactive oxygen species (ROS) production.…”
Section: Introductionmentioning
confidence: 99%
“…8a). Previous studies on NIH/3T3 cell line using brown seaweed Sargassum muticum aqueous extract showed no toxicity at 24 hrs [53]. The cell viability was reduced in a dose-dependent manner in HepG2 cell line, and the IC50 of the nanoparticles was observed at concentrations of 173.8±0.84 µg/mL.…”
Section: Anticancer Analysismentioning
confidence: 78%